2005
DOI: 10.1161/circulationaha.105.547893
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous Conduction in Mouse Bundle Branches Is Caused by Bundle-Branch Architecture

Abstract: Background-Recordings of the electrical activity of mouse bundle branches (BBs) suggest reduced conduction velocity (CV) in the midseptal compared with the proximal part of the BB. The present study was performed to elucidate the mechanism responsible for this slowing of conduction. Methods and Results-Hearts of 16 mice were isolated and Langendorff perfused. After the right and left ventricular free walls were removed, the extracellular activity of the BB was mapped with a 247-point electrode. Premature stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…It is also known that during developmental stages of the rodent heart two other gap junction isoforms (Cx40 and Cx45) can be expressed by ventricular cardiomyocytes [19], [20]. These isoforms form in the adult stage the gap junctions within the specialized cardiac conduction system [21]. In our specimen, labeling against Cx40 did not reveal intercellular signals between the cardiomyocytes rather than positive signals only in the endothelium of the vessels (data not shown).…”
Section: Discussionsupporting
confidence: 46%
“…It is also known that during developmental stages of the rodent heart two other gap junction isoforms (Cx40 and Cx45) can be expressed by ventricular cardiomyocytes [19], [20]. These isoforms form in the adult stage the gap junctions within the specialized cardiac conduction system [21]. In our specimen, labeling against Cx40 did not reveal intercellular signals between the cardiomyocytes rather than positive signals only in the endothelium of the vessels (data not shown).…”
Section: Discussionsupporting
confidence: 46%
“…We found that expression of Cx40 and Na v 1.5 was drastically reduced in the VCS after removal of Tbx5 ( Figure 5). The proximal AV bundle and distal AV bundle/bundle branches were identified by their anatomic location, acetylcholinesterase activity (12,(17)(18)(19), and contactin-2 expression (20). Tbx5 fl/fl controls demonstrated high Cx40 and Na v 1.5 expression throughout the molecularly defined VCS, whereas Tbx5 minKCreERT2 animals demonstrated dramatic Values are mean ± SD.…”
Section: Figurementioning
confidence: 99%
“…However, 8- to 10-week-old Scn5a ± mice have several cardiac electrical defects such as decreased atrial and atrioventricular conduction and increased susceptibility to pacing-induced ventricular arrhythmias (Papadatos et al, 2002). Following this initial report, the model was further analyzed to investigate the potential pathophysiological mechanisms involved in the progressive evolution of SCN5A -related PCCD (Royer et al, 2005; van Veen et al, 2005). It was found that in addition to atrial and atrioventricular conduction, ventricular conduction was also decreased.…”
Section: A Model For the Brugada Syndrome And Conduction Disorders: Tmentioning
confidence: 99%